Settlement of Land Disputes Certificate of Ownership Rights Number 251/Mojosongo Subdistrict Jebres District Surakarta City Review of General Principles of Good Government In Law Number 30 Of 2014 Concerning Government Administration: (Study of State Administrative Court Decision 48/G/2023/PTUN.SMG) - Dzaini Wardi, Ali; Maskur, Ali (Dinasti Research, 2024)
This research aims to determine the Settlement of Land Disputes, Ownership Certificate Number 251/Mojosongo Subdistrict, which can be called SHM No. 251/KM (OC No. 251/MS) through an approach to the principles contained in State Administrative Law in Law Number 30 of 2014 concerning Government Administration. This article uses a juridical-normative research method with library data sources and regulations related to legal documents. The results of this research are Land Dispute Settlement OC No. 251/MSfollowing the General Principles of Good Government (AUPB/GPGG) in the Government Administration Law so that the Semarang TUN court decision following the Principles of Justice, Usefulness, and Legal Certainty under Law Number 5 of 1986 concerning Administrative Courts State (PTUN), findings in related research also show that there are several deviations in the issuance of Land Ownership Certificates which are shortcomings of the Government Agency, namely the National Land Agency, in this case, SHM No. 251/KM includes Fictitious SHM, so it should be necessary to enforce, determine, protect the Law and related facilities more strictly and thoroughly in the Issuance of Ownership Certificate by the relevant agencies as well as fairer and more transparent law enforcement by the Semarang PTUN so that it complies with the Law. PTUN and State Administrative Law, as well as applicable Constitutional Law.